The Efforts of Handling English Learning Process for Inclusive Students at Elementary Schools in Bengkulu City - Safitri Nur Fauziah; Dian Susyla; Ria Angraini; Washlurachim Safitri (Edu-Ling: Journal of English Education and Linguistics, 2023)
The objectives of this research were to determine the efforts of handling English learning process for inclusive students at elementary schools in Bengkulu City. This study used qualitative method. The objects of this study were SD Alam Mahira Bengkulu and SDIT Al Aufa Bengkulu. The data were analyzed by using the procedures of Miles and Huberman (2014) namely; data reduction, display data, and Verification and conclusion. The results of this study showed that; (1) there were the efforts of handling English learning process for inclusive students at elementary schools in Bengkulu City such as conducting assessments, carrying out individual learning and therapy. (2) the obstacles in dealing with inclusive students found on teacher resources, lack of cooperation between parents and schools, and the emotional condition of inclusive students, (3) schools’ efforts make to deal with inclusive students were conducted by providing training for teachers and shadow teachers and the existence of special guidance teacher or inclusion coordinator. In conclusion the presence of inclusive students means that schools must be able to provide more efforts to ensure that all students receive services that are appropriate to their needs and abilities. Keywords: Effort, Elementary Schools, Handling, Inclusive Students